Strengthening routine health data analysis in Ethiopia: the Operational Research and Coaching for Analysts (ORCA) experience - Joanna Busza; Seblewengel Lemma; Annika Janson; Serawit Omar Adem; Della Berhanu; Atkure Defar; Lars-Åke Persson; Carina Källestål (Taylor & Francis Group, 2021)
Many routine health information systems (RHIS) show persistent gaps between recording and reporting data and their effective use in solving problems. Strengthening RHIS has become a global priority to track and address national health goals. In Ethiopia, the Ministry of Health and Bill & Melinda Gates Foundation introduced the Operational Research and Coaching for Analysts (ORCA) capacity development project, co-designed with the London School of Hygiene & Tropical Medicine, which delivered training, coaching and mentoring support. We present the development, experiences, and perceptions of ORCA as a mechanism to enhance data quality, analysis, interpretation and use. ORCA integrated capacity development activities into national data analysts' routine workload over a period of 2 years. Participating analysts were drawn from across the Ministry of Health directorates and two of its closely aligned agencies: the Ethiopian Public Health Institute and the Ethiopian Pharmaceutical Supply Agency. We used mixed methods (knowledge questionnaire, semi-structured interviews, programme records) to document the fidelity, feasibility, reach, and acceptability of ORCA and identify early signs of improved knowledge and changing institutional practices. Thirty-six participants completed the programme. Working in interdisciplinary groups on specific national health indicators, they received training workshops and support for study design, fieldwork, and analysis to build skills in assessing data quality and interpreting findings relevant to policy. Personal development grants and laptops provided incentives for sustained engagement. Participants appreciated ORCA's applied and practical approach as well as good communication from administrators and clear links to national strategy. They also expressed frustration with delays, difficulties prioritising project work over routine responsibilities, and lack of formal accreditation. Knowledge and analytic skills increased and participants were able to integrate experiences from the project into their future work. Health system managers saw potential in longer-term improvements in data analysis and application to policy, although no clear changes were observed yet.